TRANSFORMASI PELAYANAN INFORMASI PUBLIK HUMAS PEMERINTAH KOTA TANGERANG DI ERA 4.0 - Nurmalita Chairani (2020)
The Industrial Revolution 4.0 is an era of digitalization that has resulted in changes in the behavior and lifestyle of both individuals and organizations. Various industries must prepare themselves to face and adapt to technological developments, public relations one of which is affected by industry 4.0. technological development and the openness of information flow identified as environmental factors affecting an organization, public relations must be prepared to be in line with the Internet of Things. This study aims to analyze the transformation of public information services by Tangerang City Government public relations as a provider of public information services as well as the obstacles and challenges faced. This research uses a qualitative. Data collection techniques used were interviews. The results showed that the changes in public information services made were planned changes. This is because changes are made according to the level of needs or mobility of the people of Tangerang City towards information needs. In addition, adjusting the law regarding public information disclosure. As well as the times that make government public relations to always develop to be able to maximize information services to the public, so that the form of public information services is carried out using more of the internet of things.